Effects of Environmental Pollutants on MCF‐7 Cells: A Metabolic Approach. Issue 2 (12th July 2016) - Norberto, Sónia; Calhau, Conceição; Pestana, Diogo; Faria, Ana
ABSTRACT: Several environmental pollutants (EPs) have been associated with biological and molecular processes leading to adverse human health effects, including different types of cancer. Nevertheless, the effects exerted on tumor glucose metabolism are unclear. To evaluate the effects on cellular and molecular mechanisms, namely glucose metabolism, MCF‐7 cells were exposed to EPs during short‐ and long‐term exposures. The effect of both, organochlorine pesticides and plasticizing agents, on glucose uptake by MCF‐7 cells was not dose‐dependent and was affected by time of exposure. The ΣHCH and BPA increased glucose uptake after 20 min. Long‐term exposure to 250 nM of organochlorine pesticides ( p, p′ ‐DDE and ΣHCH) and BPA increased cell proliferation. However, only the organochlorine pesticides were able to increase lactate production, without a concomitant higher glucose uptake or glycolytic enzymes transcription. Given their distinct persistent profiles, the biological significance of their exposure should be considered accordingly. J. Cell. Biochem. 118: 366–375, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Environmental pollutants were able to influence glucose uptake metabolism. Organochlorine pesticides and plasticizing agents effect on glucose uptake was affected by time of exposure. Effects on tumor biology may be influenced by compound type and exposure pattern.